Revolutionizing disease modeling: the emergence of organoids in cellular systems - Pedrosa, Ana Rita Silva (2023)
Cellular models have created opportunities to explore the characteristics of human diseases through well-established protocols, while avoiding the ethical restrictions associated with post-mortem studies and the costs associated with researching animal models. The capability of cell reprogramming, such as induced pluripotent stem cells (iPSCs) technology, solved the complications associated with human embryonic stem cells (hESC) usage. Moreover, iPSCs made significant contributions for human medicine, such as in diagnosis, therapeutic and regenerative medicine. The two-dimensional (2D) models allowed for monolayer cellular culture in vitro; however, they were surpassed by the three-dimensional (3D) cell culture system. The 3D cell culture provides higher cell–cell contact and a multi-layered cell culture, which more closely respects cellular morphology and polarity. It is more tightly able to resemble conditions in vivo and a closer approach to the architecture of human tissues, such as human organoids. Organoids are 3D cellular structures that mimic the architecture and function of native tissues. They are generated in vitro from stem cells or differentiated cells, such as epithelial or neural cells, and are used to study organ development, disease modeling, and drug discovery. Organoids have become a powerful tool for understanding the cellular and molecular mechanisms underlying human physiology, providing new insights into the pathogenesis of cancer, metabolic diseases, and brain disorders. Although organoid technology is up-and-coming, it also has some limitations that require improvements.